Who's who: How uncertainty about the favored group effects outcomes of affirmative action - Chi Trieu (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2023)
When affirmative action policies target more than one disadvantaged group, they contain uncertainty as to whether an individual who belongs to one of these groups was actually favored. In a laboratory experiment, we study how this feature affects outcomes of affirmative action in the form of quotas, and compare it with two other conditions, namely affirmative action with a certain favored group and no affirmative action. We find that when a group is favored with certainty and the social identity that triggers affirmative action is made salient, affirmed individuals are wrongly perceived as less competent, both by themselves and by others. Consequently, their willingness to compete does not increase and they are selected less for teamwork post competition. Affirmative action with uncertain favored groups does not distort belief in competence, and thus does not induce such unintended consequences. In contrast, it increases competition entry of the affirmed groups and enhances their chances of being selected for teamwork.
Keywords: C91; D02; J71; 330; Affirmative action; Competition; Uncertainty; Identity; Experiment